Integrating health, sustainability, and vocational competencies in maritime education for future seafarers - Larsen Barasa; Tri Cahyadi; April Gunawan Malau; Marihot Simanjuntak; Suhartini Suhartini; Susi Herawati; Natanael Suranta; Bambang Kurniadi; Marudut Bernadtua Simanjuntak (Physical Therapy Journal of Indonesia, 2025)
Background: The maritime industry's increasing emphasis on holistic well-being and environmental responsibility necessitates a reevaluation of traditional training methods. This research evaluates maritime education program effectiveness in preparing cadets for industry demands, uniquely integrating health and sustainability with vocational competencies. This study aimed to evaluate the adequacy of current maritime education in preparing cadets for the physical, mental, and vocational demands of seafaring, and to identify methods for better integrating health and sustainability into the curriculum. Methods: This qualitative study explored cadet preparedness in maritime education, focusing on health, sustainability, and vocational competencies. Data were collected through semi-structured interviews with 30 participants, including maritime experts, lecturers, and graduates, selected for their diverse perspectives. Classroom and training observations supplemented interview data, providing a holistic view of current practices. Thematic analysis was employed to identify key themes related to competency development and sustainability, allowing for cross-group comparisons. Finally, narrative synthesis integrated findings into a cohesive understanding of how maritime education can better prepare future seafarers. This multi-method approach ensured a comprehensive and triangulated dataset, enhancing the robustness of the research findings. Results: The results indicate that current programs effectively prepare cadets for physical and vocational challenges, and sustainability practices are incorporated. However, there is a need for enhanced mental health support and deeper integration of contemporary sustainability practices. Conclusions: To ensure a resilient and sustainable workforce in the evolving maritime industry, it is crucial to refine maritime education by balancing physical, mental, and vocational competencies with comprehensive sustainability training.